Three-dimensional magnetohydrodynamic two-phase flow and heat transfer analysis in electroslag remelting process. (5th April 2015) - Wang, Qiang; Zhao, Ruijie; Fafard, Mario; Li, Baokuan
Abstract: A transient three-dimensional (3D) coupled mathematical model is developed in this paper in order to explore the electromagnetic, flow, and temperature fields, as well as the solidification in the electroslag remelting (ESR) process. Maxwell's equations are solved by the Finite Volume Method. The Joule heating and electromagnetic force (EMF), the source terms in the energy and momentum equations, are recalculated during each iteration as function of the phase distribution. The movement of the metal droplets is described by the Volume of Fluid (VOF) approach. Additionally, the solidification of the metal is modeled by an enthalpy-based technique, where the mushy zone is treated as a porous medium with a porosity equal to the liquid fraction. The results show that the electric current tends to go through the metal droplet first. The EMF varies with the falling metal droplet, always blocking the motion of the metal droplet. The zone with the highest temperature appears under the outer radius of the inlet. A larger Joule heating density, as well as a higher average temperature of the molten slag, is obtained when the current increases. Bigger metal droplets form with more heat and momentum, resulting in a deeper liquid metal pool. Highlights: First time to develop a transient 3D coupled mathematical model of the ESR process. Variation of Joule heating and EMF with the falling metal droplet is demonstrated. Asymmetrical physical fields are revealed indicating the necessity of a 3D model. The effect of the current on the heat transfer and MHD flow is clarified.